The effects of Rumensin® and two levels of energy prior to calving on reproductive performance in first calf heifers - L.R. Sprott; L.R. Corah; Jack G. Riley; G.H. Kiracofe (Kansas Agricultural Experiment Station Research Reports, 1981)
Heifers fed low energy diets gained less before calving, took longer from calving to first estrus, and dropped lighter calves. Their conception rates were lower and fewer showed estrus the first 20 days of breeding. Rumensin lengthened the time from calving to estrus with no effect on calf birth weight, milk production, or percentage of calves weaned. However, calves from heifers fed Rumensin gained faster. Long-term Rumensin feeding to heifers (from weaning through second breeding) increased weight gain and hastened puberty with no effect on reproductive performance. Rumensin-fed dams tended to wean heavier calves.
Keywords: Cattlemen' s Day; 1981; Report of progress (Kansas State University. Agricultural Experiment Station); 394; Beef; Energy; Reproductive performance; Heifers